2021
DOI: 10.1155/2021/6651099
|View full text |Cite
|
Sign up to set email alerts
|

Failure Mechanism and Control of Lower Retracement Channel in Close‐Distance Double‐Thick Coal Seams

Abstract: Under the condition of close-distance double-thick coal seams’ mining, the serious strata behavior occurred in the lower retracement channel, which is affected by the double disturbance with upper coal-pillar static load and mining dynamic pressure. Field investigation, laboratory test, and numerical simulation were used to study the failure characteristics and stress distribution of N0381 retracement channel. The results show that the plastic failure and stress of the surrounding rock are obviously asymmetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Therefore, the double‐yield model was used to simulate the mechanical properties of gob gangue. The double‐yield parameters were obtained by using trial and error, 33 as shown in Tables 3 and 4. Numerical model validation…”
Section: Numerical Simulation Analysis On Deformation and Failure Mec...mentioning
confidence: 99%
“…Therefore, the double‐yield model was used to simulate the mechanical properties of gob gangue. The double‐yield parameters were obtained by using trial and error, 33 as shown in Tables 3 and 4. Numerical model validation…”
Section: Numerical Simulation Analysis On Deformation and Failure Mec...mentioning
confidence: 99%
“…Many scholars have widely researched on ground pressure in the working face of close-distance coal seams [11][12][13]. Shang studied the destruction process of the lower coal seam chain pillar and gate road under the action of the coal pillar in close-distance coal seam mining [14].…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] During the working face life cycle, it is indispensable to safely and efficiently mine extra-thick coal seams while stopping and withdrawing the supports at a suitable location is the most crucial step to end the cycle. [22][23][24] The stopping mining line of the working face is also called the terminal mining line, which is the position where the longwall working face stops coal mining and withdraws the supports. 25 The supports are evacuated from the retracement channel, and the supports' area and the channel's area form a large section of the roadway during the stopping period (LSRSP).…”
Section: Introductionmentioning
confidence: 99%
“…During the working face life cycle, it is indispensable to safely and efficiently mine extra‐thick coal seams while stopping and withdrawing the supports at a suitable location is the most crucial step to end the cycle 22–24 . The stopping mining line of the working face is also called the terminal mining line, which is the position where the longwall working face stops coal mining and withdraws the supports 25 .…”
Section: Introductionmentioning
confidence: 99%